PENGARUH PENGUASAAN PEMBELAJARAN AQIDAH AKHLAK TERHADAP PERILAKU SISWA KELAS VIII DI MADRASAH TSANAWIYAH DARUL FALAH SINGOSARI MALANG - Ainus Said; Ika Ratih Sulistiani Sulistiani; Khoirul Asfiyak (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This studi was conducted to measure the efect of how much mastery of moral learning on the behavior of students in Darul Falah MTs Singosari Malang, which began in April 2019. The sample in this study was class VIII, which amounted to 19 students. Data obtained by conducting questionnaires and interviews, and prerequisite test analysis techniques using the normality test and homogeneity test. While the hipothesis formulation testing tecnique as the data measurement power using the product moment correlation test. Form the results of this study prove or state that there is an innfluence between mastery of moral aqidah learning on student behavior based on the calculation, rxy at the significance level of 5% greater than r table or rt = (0.486>0.456) which means the work hipothesis is acepted and the null hipothesis is rejected.Keywords: influence, learning morality, and student behavior